Identification of a mycorrhiza isolate from Paphiopedilum Barbatum (Lindl.) pfitzer from ex situ location and determination of its growth-enhancing capabilities - Nurul Aliaa Idris (Fakulti Sains dan Teknologi, 2012)
Orchids and mycorrhiza are known to have a symbiotic relationship that function particularly in seed germination and also in promoting overall plant growth. It is believed that a certain orchid mycorrhiza that functions to enhance plant growth also lives symbiotically in the roots of Paphiopedilum barbatum.